2002
DOI: 10.2135/cropsci2002.1369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of purity of rice hybrids using microsatellite and STS markers

Abstract: The estimation of hybrid rice seed purity is done conventionally by the grow out test (GOT), which is based on the assessment of morphological and floral characteristics in plants grown to maturity. For seed companies, large amounts of capital are locked up in the form of hybrid seed stock while awaiting the results of the GOT. With the objective of replacing the GOT with DNA based assays, cytoplasmic male sterile (CMS), restorer, and hybrid lines have been screened by means of microsatellite and sequence tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 16 publications
3
63
0
3
Order By: Relevance
“…The SSR markers identified for true hybrids development in CO2 × MNga-1 population were specific to this cross combination, for new crosses similar kind of homologous markers need to be identified. Similar findings were reported for identifying true hybrids in rice (Ye-yun et al 2005, Yashitola et al 2002, Hashemi et al 2009), cotton (Wu et al 2001, Asif et al 2009, Dongre et al 2011, peanut (Gomez et al 2008), sugarcane (Manigbas andVillegas 2004, Zhang et al 2009), sunflower (Iqbal et al 2010), oilpalm (Thawaro and Te-chato 2009) and cabbage (Liu et al 2007). In all the above studies SSR markers were used for germplasm identification, cultivar fingerprinting, true hybrid identification, genetic purity testing, parentage confirmation of hybrids, and identify heterotic pattern in hybrids.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The SSR markers identified for true hybrids development in CO2 × MNga-1 population were specific to this cross combination, for new crosses similar kind of homologous markers need to be identified. Similar findings were reported for identifying true hybrids in rice (Ye-yun et al 2005, Yashitola et al 2002, Hashemi et al 2009), cotton (Wu et al 2001, Asif et al 2009, Dongre et al 2011, peanut (Gomez et al 2008), sugarcane (Manigbas andVillegas 2004, Zhang et al 2009), sunflower (Iqbal et al 2010), oilpalm (Thawaro and Te-chato 2009) and cabbage (Liu et al 2007). In all the above studies SSR markers were used for germplasm identification, cultivar fingerprinting, true hybrid identification, genetic purity testing, parentage confirmation of hybrids, and identify heterotic pattern in hybrids.…”
Section: Resultssupporting
confidence: 62%
“…markers in rice (Yashitola et al 2002, Hashemi et al 2009), cotton (Wu et al 2001, Asif et al 2009, Dongre et al 2011, peanut (Gomez et al 2008), sugarcane (Zhang et al 2009), sunflower (Iqbal et al 2010) and cabbage (Liu et al 2007). Bianco et al (2011) used ISSR markers for identification of F 1 hybrids in artichoke and suggested that morphological trait alone is not sufficient to evaluate the offspring precisely.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mao (1998) and Kumar (2012) every one percent of impurity in hybrid seeds could reduce the yield upto 100 kg per ha . The area of the most concern for the future hybrid rice programme is the long-term maintenance of the genetic purity of the hybrid, parental lines (A, B and R lines) and also maintenance of high level of genetic purity in hybrids is essential to exploit the moderate level of heterosis observed in crop (Yashitola , 2002;Nandkumar , 2004). Thus, there is a need to assess the genetic purity of hybrid seeds in quick succession so that seeds produced in dry season could reach the farmers for commercial cultivation in very next wet season.…”
Section: Rice (mentioning
confidence: 99%
“…Molecular markers, in contrast, offer an impartial means for precise molecular profiling of -1 varieties/hybrids and their purity assessment in short span of time (Rehem , 2010). Microsatellite (SSR/ STMS) marker based high level of polymorphism or fingerprinting assays have now emerged as one of the new and rapid technology for cultivar/ impurity identification to replace/ supplement the conventional grow-out test grow out test (Yashitola , 2002;Yifru ., 2006;Lu ., 2009;Bora 2016). Cytoplasmic male sterile (CMS-A line), maintainer (B-line), restorer (R-line) lines and their hybrids have been screened by a number of microsatellite and sequence tagged site markers by several workers (Sundaram 2008 ;Jaikishan , 2010; Therefore, keeping in view of the above facts, the objective of the present study was to estimate and identify the level of purity in seed lots of nine rice hybrids with their parental lines through microsatellite markers based DNA fingerprints and grow out test, and also to establish the basis for identification, authentication, protection and monitoring of seed purity for hybrids evaluated.…”
Section: Rice (mentioning
confidence: 99%
“…STS được sử dụng cho nghiên cứu đa dạng di truyền [139], nhận biết gen [89], so sánh bản đồ [25], xác định gen liên kết [125], xác định độ thuần hạt lai [206] và đánh giá tính kháng bệnh [13].…”
Section: Kỹ Thuật Vị Trí Chuỗi đáNh Dấu (Sequencetagged Sites-sts)unclassified